2008
DOI: 10.1563/1548-1336(2008)34[203:cipiap]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Guided Implant Placement in a Patient With Severe Atrophy

Abstract: Computer software associated with imaging techniques facilitates diagnosis, planning, and management in cases of severe maxillary atrophy, by reducing the incidence of complications and improving the postoperative course and functional outcome. This article reports on a case of a 66-year-old woman with maxillary atrophy. Computer software was used to plan and position 6 maxillary and 4 mandibular implants, taking maximum advantage of the remaining bone. Bicorticalization was sought by angulation and implant fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…12 However, positive results were also found in another study, that showed reduction of standard deviation with consequent decrease in surgical errors, with the improvement in the coronal osteotomy from 1.5 to 0.9 mm, apical positioning improvement and better angulation from 8° to 4.5°. 13 The most commonly complications in guided surgery are: incorrect perforation of bone tissue, implants loss, maladjustment of prosthetic components and prosthesis loss. These complications may be the result from errors in the various stages of surgical preparation that involves imaging scanning, surgical guideplanning, and even their fi xation during the site preparation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12 However, positive results were also found in another study, that showed reduction of standard deviation with consequent decrease in surgical errors, with the improvement in the coronal osteotomy from 1.5 to 0.9 mm, apical positioning improvement and better angulation from 8° to 4.5°. 13 The most commonly complications in guided surgery are: incorrect perforation of bone tissue, implants loss, maladjustment of prosthetic components and prosthesis loss. These complications may be the result from errors in the various stages of surgical preparation that involves imaging scanning, surgical guideplanning, and even their fi xation during the site preparation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3). 22,23 Computer-assisted surgery offers the clinician numerous advantages in implant-prosthetic rehabilitation in totally or partially edentulous patients, such as visualization of anatomic structures, evaluation of implant position and inclination, easier and more accurate implant insertion, and the possibility of using prefabricated prostheses. 12 In this article, we present a case report of a patient with a cleft palate and other bone defects who we decided to treat in 2 steps: the first consisted of a bone graft from the iliac crest and 2 zygomatic implants, 20 and the second comprised 4 maxillary implants and the immediate loading of the provisional prosthesis with the aid of a computer-assisted surgery (Fig.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Morphologically, the basal cortical mandible´s bone, in the anterior segment, is thicker than the buccal and lingual cortical plates 5 , so bicorticalization promotes greater primary stability, due to greater contact between the implant and this basal bone, and can be applied in various regions of the oral cavity where the bone quality indicates poor prognoses for implant stabilization 2 , 6 ; however, they are associated with higher rates of implant fractures than monocortical implants 7 , and has also been associated with the computer-guided installation of implants in atrophic jaws 6 .…”
Section: Introductionmentioning
confidence: 99%